2022
DOI: 10.1159/000524954
|View full text |Cite
|
Sign up to set email alerts
|

Regorafenib beyond the Second Line in Relapsed Glioblastoma: A Case Report and Literature Review

Abstract: Glioblastoma multiforme (GBM) is one of the most frequent and aggressive primary tumors in the central nervous system, representing more than 60% of all brain tumors in adults. Primary GBM remains incurable with a poor prognosis both for limited therapeutic alternatives and for a high risk of progression or recurrence. In fact, at recurrence, the few treatment options available, and often characterized by limited effectiveness, have always been an Achilles’ heel. The recent approval of second line of regorafen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…For effective and lasting treatment, strategies should focus not only on overcoming MDR but eradicating MDR cancer as well. Recently, regorafenib (RF) has been approved by FDA for treatment of recurrent glioblastoma (REGOMA) [7]. Phase II trials of REGOMA with RF has shown better overall survival (OS) compared to other drugs in use [8].…”
Section: Introductionmentioning
confidence: 99%
“…For effective and lasting treatment, strategies should focus not only on overcoming MDR but eradicating MDR cancer as well. Recently, regorafenib (RF) has been approved by FDA for treatment of recurrent glioblastoma (REGOMA) [7]. Phase II trials of REGOMA with RF has shown better overall survival (OS) compared to other drugs in use [8].…”
Section: Introductionmentioning
confidence: 99%